Upaya Mengatasi bahaya Pernikahan Dini dan Kenakalan Remaja di Desa Gunung, Kecamatan Simo, Boyolali - Yanitama, Arka; Rafael Eben Haezer Ginting; Tanti Liana Dewi; Umi Sa’adah; Charles Sahalatua Pangaribuan (Jurnal Dharma Indonesia, 2024)
Early marriage and juvenile delinquency are two phenomena that often traverse different paths but have the potential to cast a dark shadow on the social development of society. Early marriage and juvenile delinquency are not simply social phenomena that can be ignored; both haunt the future of the younger generation and place a heavy burden on the well-being of society as a whole. In this article, we will explore in depth the dangers of early marriage and juvenile delinquency, uncover the roots of the problem, and detail the negative impacts on individual and societal development. In this community activity, the UNNES GIAT 6 KKN Team and the Gunung Village Government collaborated to carry out an outreach with the theme "The Dangers of Early Marriage and Juvenile Delinquency" which was held on Sunday 26 November 2023 at the courtyard of the Gunung Village Hall. In this activity several methods were applied, namely brain storming, lectures by presenters or resource persons, discussions with participants, and quizzes with prizes held by KKN students. Religious leaders have an important role in preventing early marriage and juvenile delinquency. In dealing with the phenomenon of early marriage and juvenile delinquency, religious leaders in Gunung Village can provide moral guidance, religious values and educational approaches to teenagers to minimize risks. Religious and ethical education, religious leaders can play a role in protecting teenagers from the dangers posed by early marriage and juvenile delinquency, so the support of religious leaders is needed. Some of the roles of religious leaders in dealing with the dangers of early marriage and juvenile delinquency are moral and ethical approaches, spiritual guidance, religious and ethical education, prevention of early marriage, women's empowerment.